Utility of blood smear and bone marrow smear examination in autopsy practice: A preliminary observation (Indian Internet Journal of Forensic Medicine and Toxicology, 2011)
Autopsy diagnosis rests on observation of gross anatomical features, microscopic examination and toxicological analysis. However, certain diseases need additional laboratory procedures for confirming diagnosis or ruling out diagnosis. Examination of blood film and bone marrow smear has considerable diagnostic and therapeutic importance in clinical setup. In the present study we have found encouraging morphologicalfindings in blood and bone marrow smears for arriving at diagnosis in few conditions and the method can be utilized as supplementary laboratory procedure for confirming or ruling out diagnosis.
Keywords: autopsy; death; bone marrow; blood smear; diagnosis